1995
DOI: 10.1093/humrep/10.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Triggering of ovulation in human menopausal gonadotrophin-stimulated cycles: comparison between intravenously administered gonadotrophin-releasing hormone (100 and 500  g), GnRH agonist (buserelin, 500  g) and human chorionic gonadotrophin (10 000 IU)

Abstract: We studied the peri-ovulatory and luteal phases in 38 human menopausal gonadotrophin (HMG)-stimulated cycles, in which ovulation was triggered with four different i.v. bolus ovulation triggers: 100 micrograms gonadotrophin-releasing hormone (GnRH; group A, n = 9), 500 micrograms GnRH agonist (GnRHa; group B, n = 10), 10,000 IU human chorionic gonadotrophin (HCG; group C, n = 10) and 500 micrograms GnRH (group D, n = 9). Endogenous luteinizing hormone (LH) surges occurred in all cycles of groups A, B and D. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 0 publications
1
6
1
1
Order By: Relevance
“…Our results parallel those described in IVF-ET (4,8,9,12,13) and indicate that corpus luteum performance is seriously affected when ovulation is induced with GnRH agonist.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results parallel those described in IVF-ET (4,8,9,12,13) and indicate that corpus luteum performance is seriously affected when ovulation is induced with GnRH agonist.…”
Section: Discussionsupporting
confidence: 88%
“…Although luteolysis induced by GnRH agonist does not exclude the possibility of OHSS (9,30,31), in our study none of the donors that ovulated with the GnRH agonist suffered from OHSS; on the other hand, four cases of mild OHSS were detected in the group of donors receiving rhCG (Table 1). Therefore, in our opinion, the use of GnRH agonist instead of hCG to induce final oocyte maturation can be a good alternative to avoid OHSS in assisted reproduction treatments (1,4,6,31).…”
Section: Discussioncontrasting
confidence: 59%
“…Lanzone et al (78) and Imoedemhe et al (79) were the fi rst to report the successful use of GnRH-a for induction of an endogenous LH/FSH surge for fi nal follicular maturation following exogenous gonadotropin stimulation of the ovaries. Since then, there have been numerous reports of the successful use of GnRH-a to successfully induce follicular maturation in IVF cycles (80,81), as well as ovulation in non-IVF cycles (82,83).…”
Section: Gnrh-agonists and Ohssmentioning
confidence: 99%
“…Gerris et al also reported the occurrence of moderate OHSS in one patient following GnRH-a administration (82), but in this case native GnRH was used, resulting in successful ovulation triggering but without the critical ovarian suppression which is thought to be at least equally important in the prevention of OHSS (91). Casper surveyed a total of 163 cycles in which GnRH-a was used to trigger ovulation in the context of preventing OHSS (92).…”
Section: Recombinant Lh and Ohssmentioning
confidence: 99%
“…Comme nous l'avons vu, l'hCG possède un effet biologique beaucoup plus intense que la LH sur une durée de plus de six jours [117]. Gerris et al [118] rapportent des taux d'estradiol et de progestérone beaucoup plus élevés après l'injection d'hCG par rapport à un agoniste de la GnRH. Les doses d'hCG évaluées dans la littérature vont de 2000 à 25 000 UI.…”
Section: Modalités Du Déclenchementunclassified